Proteomic Identification of Early Biomarkers of Acute Kidney Injury After Cardiac Surgery in Children - Devarajan, Prasad (2010)
BACKGROUND: Serum creatinine is a delayed marker of acute kidney injury (AKI). Our purpose was to discover and validate novel early urinary biomarkers of AKI after cardiac surgery. STUDY DESIGN: Diagnostic test study. SETTING & PARTICIPANTS: Children undergoing cardiopulmonary bypass surgery. The test set included 15 subjects with AKI and 15 matched controls (median age 1.5 years) among 45 subjects without AKI. The validation set included 365 children (median age 1.9 years). INDEX TESTS: Biomarkers identified by proteomic profiling: α(1)-microglobulin, α(1)-acid glycoprotein, and albumin. REFERENCE TEST: AKI, defined as a 50% or greater increase in serum creatinine from baseline within three days of surgery. RESULTS: Proteomic profiling by SELDI-TOF MS revealed three protein peaks that consistently appeared within 2 hours in children who developed AKI after cardiopulmonary bypass surgery. The proteins were identified as α(1)-microglobulin, α(1)-acid glycoprotein, and albumin. Using clinical assays, the results were confirmed in a test set and validated in an independent prospective cohort. In the validation set, 135 (37%) developed AKI, in whom there was a progressive increase in urinary biomarker concentrations with severity of AKI. The area under the curve (AUC) for urinary α(1)-microglobulin, α(1)-acid glycoprotein, and albumin at 6 hours after cardiac surgery were 0.84 (CI 0.79–0.89), 0.87 (CI 0.83–0.91), and 0.76 (CI 0.71–0.81) respectively. Subjects with increasing quartiles of biomarkers demonstrated increasing length of hospital stay and duration of AKI (P<0.001). LIMITATIONS: Single center study of children with normal kidney function at recruitment. The SELDI-TOF MS technique has limited sensitivity for the detection of proteins above the 20 kDa range. CONCLUSIONS: Urinary α(1)-microglobulin, α(1)-acid glycoprotein, and albumin represent early, accurate, inexpensive and widely available biomarkers of AKI after cardiac surgery. They also offer prognostic information on duration of AKI and length of hospitalization after cardiac surgery.